The brightest of dreams [large type] - Mason, Susan Anne (Mason, Susan Anne. Canadian crossings, 2020)
"Quinten Aspinall is determined to fulfill a promise he made to his deceased father to keep his family together. To do so, he must travel to Canada to find his younger siblings, who were sent there as indentured workers while Quinn was away at war. He is also solicited by his employer to look for the man's niece who ran off with a Canadian soldier. If Quinn can bring Julia back, he will receive his own tenant farm, enabling him to provide a home for his ailing mother and siblings. Julia Holloway's decision to come to Toronto has been met with disaster. When her uncle's employee rescues her from a bad situation, she fears she can never repay Quinn's kindness. So when he asks her to help find his sister, she agrees. Soon after, however, Julia receives some devastating news that changes everything. Torn between reuniting his family and protecting Julia, will Quinn have to sacrifice his chance at happiness to finally keep his promise?"--